2007
DOI: 10.4278/0890-1171-21.4s.363
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personal Values, Urban Form, and Auto Availability in the Analysis of Walking for Transportation

Abstract: Positive attitudes about urban attributes, living in a supportive neighborhood, and low automobile availability significantly predicted more walking for transportation. A framework for further research is proposed in which a factor representing the role of the automobile is examined explicitly in addition to personal values and urban form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…This is intuitive, since socio-demographics may be viewed, in part, as being proxy measures of exposure. In this context, pedestrian travel is generally dictated by the lack of availability of other modes of travel (which is related to demographics), while bicycle travel is more associated with a choice-based decision mechanism wherein bicycling is pursued for exercise and recreation (Xing et al, 2010, Coogan et al, 2007 Overall, Census tracts with a high population density, high proportion of Hispanic residents, high proportion of the population over 19 years of age, and with low education levels are particularly vulnerable to pedestrian injuries. As indicated earlier, this could be an exposure result, but could also be related to discrimination across neighborhoods Table 5.1c provides the estimates of the cross-correlation and spatial parameters.…”
Section: A Summary Of Results and Implicationsmentioning
confidence: 99%
“…This is intuitive, since socio-demographics may be viewed, in part, as being proxy measures of exposure. In this context, pedestrian travel is generally dictated by the lack of availability of other modes of travel (which is related to demographics), while bicycle travel is more associated with a choice-based decision mechanism wherein bicycling is pursued for exercise and recreation (Xing et al, 2010, Coogan et al, 2007 Overall, Census tracts with a high population density, high proportion of Hispanic residents, high proportion of the population over 19 years of age, and with low education levels are particularly vulnerable to pedestrian injuries. As indicated earlier, this could be an exposure result, but could also be related to discrimination across neighborhoods Table 5.1c provides the estimates of the cross-correlation and spatial parameters.…”
Section: A Summary Of Results and Implicationsmentioning
confidence: 99%
“…Six studies examined the effect of se]f-se]ection (e.g., residentia] preference) (8)(9)(10)15,36,70), and four found associations of walking with environmental attributes after adjustment (8,15,36,70). To demonstrate that environmental correlates of walking are independent of individual predisposition (e.g., preference for shops within walking distance), future studies need to inelude measures of self-selection as a covariate.…”
Section: Consider Neighborhood Selectionmentioning
confidence: 97%
“…However, conceming environmental attributes, studies have examined them in various ways, depending on the focus of the study and the instrument used; some attributes were also combined to produce higher level dimensions. For instance, studies have used concepts consisting of several aspects of the environment, such as comfort (1,8), compact neighborhood (15), functionality (58,75), and activity fiiendliness (28). The term "accessibility" is used in different ways in different studies: many studies consider this as the presence of or distance to neighborhood destinations, but several studies define this as a mixture of route qualities and availability of destinations (1,40), the presence or maintenance of walking paths (57), and whether cost is involved in using recreational facilities (38).…”
mentioning
confidence: 99%
“…A recent strand of research highlights the role of personal values of this type in human decision-making related to the environment. Thus, the range of existing research includes the distinction between internal values and external values (Chryssohoidis & Krystallis, 2005), the influence of these values on behaviour (Stern et al, 1999;Coogan et al, 2007) and the impact of personal values on willingness for environmental conservation (Winter, Prozesky, & Esler, 2007).…”
Section: Personal Values Related To the Environmentmentioning
confidence: 99%
“…This change has come about largely as a result of the growing importance attached to the personal values expressed through green space use (Brown, 2005;Brown & Raymond, 2007) and to the phenomenon of place attachment or people's emotional and cognitive with their physical environment (Williams & Vaske, 2003). Several studies have already shown that the evaluation of a natural space usually reveals a person's environmental value orientation (Coogan, Karash, Adler, & Sallis, 2007;Kaltenborn & Bjerke, 2002;Stern, Dietz, Abel, Guagnano, & Kalof, 1999, among others). In exploring this last concept, researchers have focused on human attitudes and behaviour towards natural landscapes, based on the theory that they derive from underlying personal values, regarded by some as the simple principles that guide evaluations or cognitive inferences (Rokeach, 1979;González & Amérigo, 2008).…”
Section: Introductionmentioning
confidence: 96%